Computer service and repair - Roberts, Richard M.; Beatty, Adam (Tinley Park, Illinois : The Goodheart-Willcox Company, Inc., 2021)
Computer Service and Repair prepares students to take the CompTIA A+ Certification Exam as well as for careers as computer technicians. It provides the skills and basic knowledge required before pursuing studies in computer-repair fields and provides information for furthering their interests in information technology as a whole.
1. Introduction to a typical PC -- 2. Operating systems -- 3. Motherboards -- 4. Central processing unit (CPU) -- 5. Power supplies -- 6. Memory -- 7. Input devices -- 8. Video systems -- 9. Audio systems -- 10. Magnetic and solid-state storage devices -- 11. Optical storage technology -- 12. Printers -- 13. Laptops and mobile devices -- 14. Modems and transceivers -- 15. Physical security and authentication -- 16. Security applications and malware -- 17. PC troubleshooting -- 18. Data recovery -- 19. Introduction to networking -- 20. Networking communication, media, and tools -- 21. Network administration -- 22. Wide area network (WAN) -- 23. Small-office/Home-office (SOHO) networking --
Keywords: COMPUTERS